Agro-morphological, physiological and biochemical characteristics of rice subjected to cyclic water stress and potassium fertilizers - Mohd Zain, Nurul Amalina (2015)
Water deficit is a major problem in rice production due to increase scarcity of water resource. To solve this problem, the present study was conducted to determine how the use of cyclic water stress and potassium fertilizer could be used to alleviate water stress in rice. In the first experiment, a series of cyclic water stress by days [CW5, CW10, CW15, CW20, CW25 and CW30 including Control flooded (CF), control saturated (CS)] were used to investigate the effect of cyclic water stress on yield, growth,physiological and biochemical response of rice. It was found that higher duration of cyclic water stress (CW15, CW20, CW25 and CW30) had reduced grain yield, total biomass, filled spikelet, 1000 grains weight, total panicle hill-1, plant height and total tillers hill-1 and increase oxidative stress and tiller mortality. Grain yield was the highest both in CF and CS treatments and followed by CW5 and CW10 with a 14.3% difference. The application of CW10 was found to have higher yield and water use efficiency under reduction of water. In the second experiment, three rates of potassium [80 kg K2O/ha (control), 120 kg K2O/ha and 160 kg K2O/ha] and three levels of cyclic water stress (CW5, CW10 and CW15) was used to characterize the role of potassium in alleviating water stress. It was observed that rice yield, harvest index, leaf gas exchange, total chlorophyll content and relative water content was influenced by interaction effects between cyclic water stress and potassium rates. The 1000 grains weight, total biomass and water productivity was influenced by potassium rates. It was found that cyclic water stress 10 days (CW10) with potassium fertilization at 120 kg K2O/ha was the best practices in achieving higher yield with less water, maximum efficiency of photosystem II (FV/FM), 1000 grains weight, total biomass production as well as uptake of major nutrient elements (N, P, K, Ca, Mg and Fe) in rice. In the third experiment, four levels of potassium rates [Control, 80 kg K2O/ha, 120 kg K2O/ha and 160 kg K2O/ha) and two types potassium sources (KCl and K2SO4) were used to investigate the influence of potassium fertilization in minimizing the effect of cyclic water stress in rice production. It was observed that panicle dry weight hill-1, root dry weight, rice yield, Catalase activity (CAT), proline, maliondialdehyde (MDA) and harvest index was influenced by potassium rates. The leaves numbers, total tillers and 1000 grains weight were influenced by potassium types. Interaction effects (potassium rate x potassium types) was observed in shoot dry weight, leaf area, total spikelet panicle-1, net assimilation rate, transpiration rate and water use efficiency. From the study, the application either KCl or K2SO4 at 120 kg K2O/ha was efficient in minimizing yield reduction under water stress. In the fourth experiment, five treatments including (1) standard local grower’s practice (control, 80CF = 80 kg K2O/ha + control flooded); (2) 120CW15 = 120 kg K2O/ha + cyclic water stress 15 days; (3) 120DS15V = 120 kg K2O/ha + drought stress for 15 days during the vegetative stage; (4) 120DS25V = 120 kg K2O/ha + drought stress for 25 days and (5) 120DS15R = 120 kg K2O/ha + drought stress for 15 days during the reproductive stage, were evaluated to assess the effects of different water stress combined with potassium fertilization on growth, yield, leaf gas exchanges and biochemical changes in rice. It was found that rice under 120CW15 treatment showed tolerance to drought stress by having high water use efficiency, peroxidase (POX), catalase (CAT), proline, maximum efficiency of photosystem II (FV/FM) and lower minimal fluorescence (FO), compared to other treatments. Based on the result , the sub experiment was conducted to identify LEA gene relation with water stress and potassium input on rice. Three treatments were evaluated i.e. Control (control flooded + 80 kg K2O/ha), Water stress 25 days + 80 kg K2O/ha and Water stress 25 days + 120 K2O/ha to detect the expression of Late Embryogenesis Abundant (LEA) genes under water stress conditions. The result showed that imposition of 25 day water stress with 120 kg K2O/ha (WSK) was proven to reduce LEA gene expression and achieve high plant growth and yield. Meanwhile,the 25 day water stress with 80 kg K2O/ha (WS) was shown to have the highest induction of the LEA gene and lower rice yield and plant growth. From this project, it can be concluded that application of cyclic water stress and potassium fertilizer was able to mitigate water stress and maximize water use efficiency in rice.